Answer:
<em>8(x2 + 2x) = –3
</em>
<em>8(x2 + 2x + 1) = –3 + 8
</em>
<em>x = –1 Plus or minus StartRoot StartFraction 5 Over 8 EndFraction EndRoot</em>
Step-by-step explanation:
<u>Solving Quadratic Equations
</u>
Sometimes it's preferred to solve quadratic equations without the use of the known quadratic formula solver. One of the most-used methods consists of completing squares and solving for x.
We have the equation
![\displaystyle 8x^2+16x+3=0](https://tex.z-dn.net/?f=%5Cdisplaystyle%208x%5E2%2B16x%2B3%3D0)
We separate variables from constants
![\displaystyle 8x^2+16x=-3](https://tex.z-dn.net/?f=%5Cdisplaystyle%208x%5E2%2B16x%3D-3)
Taking the common factor 8
![\displaystyle 8(x^2+2x)=-3](https://tex.z-dn.net/?f=%5Cdisplaystyle%208%28x%5E2%2B2x%29%3D-3)
Completing squares in the brackets and balancing the equation in the right side
![\displaystyle 8(x^2+2x+1)=-3+8](https://tex.z-dn.net/?f=%5Cdisplaystyle%208%28x%5E2%2B2x%2B1%29%3D-3%2B8)
Factoring the perfect square
![\displaystyle 8(x+1)^2=5](https://tex.z-dn.net/?f=%5Cdisplaystyle%208%28x%2B1%29%5E2%3D5)
Isolating x
![\displaystyle (x+1)^2=\frac{5}{8}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%28x%2B1%29%5E2%3D%5Cfrac%7B5%7D%7B8%7D)
![\displaystyle (x+1)=\pm \sqrt{\frac{5}{8}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%28x%2B1%29%3D%5Cpm%20%5Csqrt%7B%5Cfrac%7B5%7D%7B8%7D%7D)
![\displaystyle x=-1\pm \sqrt{\frac{5}{8}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%3D-1%5Cpm%20%5Csqrt%7B%5Cfrac%7B5%7D%7B8%7D%7D)
We can clearly see the steps used to solve the quadratic equation are (in order and written like in the question)
8(x2 + 2x) = –3
8(x2 + 2x + 1) = –3 + 8
x = –1 Plus or minus StartRoot StartFraction 5 Over 8 EndFraction EndRoot
There are about 10 properties that you need to remember.
The present age of Ahmed and Ahmed's father is 12 and 36 respectively.
Step-by-step explanation:
Given : Ahmed's father is thrice as old as Ahmed. After 12 years, his age will be twice that of his son.
To Find : Their present age ?
Solution :
Let the Ahmed's age be 'x'.
Ahmed's father is thrice as old as Ahmed.
i.e. Ahmed's father age is '3x'
After 12 years, his age will be twice that of his son.
i.e. 3x+12 = 2(x+12)3x+12=2(x+12)
Solving the equation,
3x+12 = 2x+243x+12=2x+24
x=12x=12
So, Ahmed's age is 12.
Ahmed's father age is 3\times 12=363×12=36
Therefore, The present age of Ahmed and Ahmed's father is 12 and 36 respectively.
<h2>There
is 3 times in space of 4 times please mark as brainlist</h2>
Answer:
5.21666667
Step-by-step explanation:
yopu do the total bill divided by 3
Answer:
E
Step-by-step explanation:
If you add 22 onto the sum of all the points and divide by the amount of games (6), you get 12.